FOTO SEJARAH PADA MEDIA DIGITAL: PEWARNAAN DAN MEME BERKONTEN SEJARAH - Iman Zanatul Haeri (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
Technological developments make it easier for historical reviewers to approach historical sources. But there is a trend in Indonesian digital society to change historical sources such as historical photos as information consumption. Along with the development of the times, analog photos turned into historical photos that were present in the millennial era appeared in two ways; first coloring photo history, the second